Altas expectativas na relação professor-aluno: análise do livro “Pigmalião em sala de aula” - Ferrão, Bianca Gomes (Universidade Federal de São Carlos, 2025)
This undergraduate thesis focuses on the impact of students' perceptions of teachers' expectations on their dreams and aspirations, addressing a topic that gained relevance in the studies of Rosenthal and Jacobson in the 1960s. The objective of this study was to analyze the contributions of the book Pygmalion in the Classroom: Teacher Expectation and Pupils’ Intellectual Development by Rosenthal and Jacobson (1968) for educators, seeking to establish the relationship between teacher expectations and student performance. This learning approach emphasizes that high expectations from schools, families, and the broader community that interacts and communicates with students are essential for fostering learning. The research followed a bibliographic approach and applied content analysis methodologies to the selected book. Through this analysis, three main categories were identified: (1) "Influence on Pedagogical Work," (2) "Effects on Students," and (3) "Implications for Teaching." The findings indicated a significant impact of teachers' expectations on students' academic performance and their perception of behavior in the school environment.

Este trabajo final de curso se centra en el impacto de la percepción de los estudiantes sobre las expectativas de los docentes en sus sueños y deseos, abordando un tema que ganó relevancia en los estudios de Rosenthal y Jacobson en la década de 1960. En este estudio, el objetivo fue analizar los aportes del libro “Pigmalión en el aula: expectativas docentes y desarrollo intelectual de los estudiantes”, de Rosenthal y Jacobson (1968), para los docentes, buscando encontrar la relación entre las expectativas docentes y el desempeño de los estudiantes. Este concepto de aprendizaje resalta que las altas expectativas de las escuelas, las familias y toda la comunidad que interactúa y dialoga con los estudiantes son fundamentales para promover el aprendizaje. La investigación fue de carácter bibliográfico e incluyó procesos metodológicos de análisis de contenido del libro seleccionado. A partir del análisis del contenido del libro, fue posible definir tres categorías: la primera “Influencia en el trabajo pedagógico”, la segunda “Efectos en los estudiantes” y, la tercera, “Implicaciones para la enseñanza”. Las conclusiones apuntaron la existencia de un gran impacto de las expectativas de los docentes en el rendimiento académico y en la percepción del comportamiento de los estudiantes en el entorno escolar.
High expectations in the teacher-student relationship: analysis of the book “Pygmalion in the classroom”
Altas expectativas en la relación profesor-alumno: análisis del libro “Pigmalión en el aula”
Keywords: Melhoria da aprendizagem; Influência do professor; Motivação de aprendizagem; Relação professor-aluno; Learning improvement; Teacher influence; Learning motivation; Teacher-student relationship; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM